SISTEM INFORMASI GEOGRAFIS HOME INDUSTRI DI KABUPATEN KUDUS (Information Technology and Telematics, 2014)
ABSTRACTEconomic developments in the sanctuary cannot be separated from the influence industry. Manylarge companies are there in the Holy as PT. Djarum,Petra, PR. Breadfruit, PT. Hartono Istana Teknologi,PT. Pura Barutama. In addition to Holy also hascountless thousands of small industrial enterprises(home industry) and the medium. In addition, HomeIndustry Encouraging the growth / development of newentrepreneurs in the business industry, cooperativesand SMEs in the Holy District. GIS Application homeindustry was created to provide information about thelocation of a small industry (home industry) and ease(users) to buy these productions, with the facilitiesgiven to the (user) that facilitate the visit of the sitehome industry, such as selecting the type of functionbusinesses who provide information resultingproduction home industry in Kudus Regency desiredand also supported by other facilities that are usefulfor the (user).Keywords: GIS Web, Kudus Home Industry,Information Systems, the industry.